REALISM AND OPTIMISM IN THE NOVEL A GOLDEN WEB KISAH AHLI ANATOMI PEREMPUAN PERTAMA DI DUNIA - Rice Gusti Protomo; Oom Rohmah Syamsudin (INFERENCE: Journal of English Language Teaching, 2020)
The purpose of this paper is to describe the problems in the patriarchal society and prove the optimistic realism contained in the novel “A Golden Web” by Barbara Quick and how female characters were portrayed in the 18th century. The method to analyze the novel is content analysis and literature review from books and theories related to the novel and historical records. Using a new criticism approach, this paper examines the intrinsic elements of the story. The writer studies the elements through characters and characterizations using descriptive-analytical structures. The paper ends with descriptions of character and characterization, optimism realism, and how female characters in the 18th-century novel’ contained can be revealed.Keywords: realism; patriarchy; optimism; new criticism